Characterization of CDS Region of Exons 1 and 2 of SOX9 Gene as Potential Gene in Construction of Syrinx Structure in Junglefowl (Gallus sp.) - Alfiyan, Achmad; Farajallah, Achmad; Maria, Ulfah; Perwitasari-Farajallah, Dyah; Muladno, Muladno (Bogor Agricultural University, Indonesia, 2024)
The crowing of male Gallus exhibits diverse sound patterns. This is believed to be related to the phenotypic diversity of vocal organs, one of which is influenced by the nucleotide diversity of the associated genes. The SOX9 gene, involved in cartilaginous tissue growth and development, is reported to contribute e in the development of larynx and syrinx. This study aimed to characterize the CDS regions of exons 1 and 2 of the SOX9 gene in junglefowl to assess its diversity. Genomic DNA was extracted from ten individuals of G. varius from Lombok and Sumbawa. The CDS regions of SOX9 gene exons 1 and 2 were amplified using two primer pairs. Additionally, the CDS regions of SOX9 gene exons 1 and 2 from 54 junglefowl SRA data in an online repository were mapped and analyzed. The study identified all nucleotide sequences as CDS regions of SOX9 gene exons 1 and 2. Six shared, and 24 unique haplotypes were constructed. A putative amino acid sequence common to all Gallus species was also identified. The diversity observed in the CDS regions of SOX9 gene exons 1 and 2 nucleotide sequence showed a diﬀerent level with the diversity observed in its amino acid sequence.